Growth and survival of Macrobrachium rosenbergii with reference to temperature and hardness - Venugopal, G; Mandal, Anup; Chadha, N K; Ali, Musharraf (Indian Journal of Fisheries, 2011)
Culture of fresh water giant prawn Macrobrachium rosenbergii (de Man) has gained considerable momentum in India. Several attempts are being made to propagate and popularize fresh water prawn culture in northern India. The present work was attempted to observe the effect of low temperature regime, which prevails in northern India in winter seasons, as well as the impact of total hardness and chlorides of ground water on the growth and survival of M. rosenbergii during the rearing phase of post larvae to juveniles and juveniles to adults. Total hardness (530 ppm as CaCO3) has hampered the growth of post larvae during the two-month rearing period i.e. up to juvenile stage. The effect of temperature on survival of prawns was studied during the peak winter season by stocking the prawn in poly house (under controlled condition) as well as in nursery ponds. It was observed that in the natural ponds the minimum water temperature dropped to 90c and resulted in hundred percent mortality of prawns, whereas juveniles in the polyhouse survived under water temperature range of 14.5 to 28Â°c and recorded survival of 56% with average growth of 26.9 g.